Analysis of the Effectiveness of Material Selection for Riverside Stabilization Using the Analytical Hierarchy Process (AHP) Method: Case Study: PT. Tondano Nusajaya Mine - Tiny Mananoma; Randy Dandel; Reinaldo Christian Rembet (Journal of Engineering, Electrical and Informatics, 2025)
This research aims to evaluate the effectiveness of retaining wall construction materials for riverbank slopes at PT. Tambang Tondano Nusajaya, Likupang, North Minahasa, using the Analytical Hierarchy Process (AHP) method. The analysis was conducted on three alternative materials geocell concrete, wiremesh concrete, and reinforced steel based on three criteria: structural strength, cost efficiency, and installation speed. The AHP results indicated geocell concrete as the selected material with the highest global priority score of 0,624, excelling in installation speed 0,480 and cost efficiency 0,405, while reinforced steel and wiremesh concrete obtained lower scores of 0,164 and 0,213, respectively. The findings suggest that although reinforced steel possesses high structural reliability, operational considerations regarding time acceleration and cost optimization are more dominant in this project context. Geocell Concrete is recommended as the most effective and efficient solution for riverbank retaining wall material application at the study location, with an important note regarding the necessity of further investigation concerning long-term performance and adaptation to local environmental conditions.